Rigid Flexible Coupling Dynamics Research of the Flap Transmission Mechanism with Clearance Joints - Zhang Tao; Liu Geng; Ma Shangjun (Jixie chuandong)
In order to study the dynamic characteristics of flap transmission mechanism with clearance joints, based on an improved nonlinear normal impact force model with variable stiffness, and the elastic factor of connecting rod, the angular velocity and angular acceleration of the steering gear are simulated and analyzed with the conditions of different clearance joints （c=0、c=δ and c=1.6δ） , and different friction parameters （0.06、0.08 and 0.1）. The dynamic output angular velocity and angular acceleration of the flap transmission exhibit obvious oscillation, and the amplitude of the angular acceleration is larger than that of the angular velocity oscillation; at the same time, when the driving load changes, the angular velocity and angular acceleration fluctuate greatly, but the fluctuation degree in the case of c=0 is greater than that with clearance; in addition, the higher the friction coefficient at the clearance joint is, the greater the amplitude of angular velocity and angular acceleration oscillation are, accompanied by high-frequency oscillation and delay phenomenon.